Cystic medial degeneration of the aorta is associated with p53 accumulation, Bax upregulation, apoptotic cell death, and cell proliferation. Issue 3 (1st September 1999) - Ihling, C; Szombathy, T; Nampoothiri, K; Haendeler, J; Beyersdorf, F; Uhl, M; Zeiher, A M; Schaefer, H E
Abstract : OBJECTIVE: To address a potential role for p53, Bcl2 associated protein X (Bax), and apoptosis in the processes associated with cell turnover during cystic medial degeneration (CMD) of the aorta. METHODS: Histochemical, immunohistochemical, biochemical, and morphometric methods were used to assess the presence and distribution of p53 immunoreactivity (p53-IR) and Bax immunoreactivity (Bax-IR), as well as the presence of apoptosis and tissue repair processes. RESULTS: Immunohistochemical staining disclosed evidence for p53-IR in all specimens in 26.1 (11.5)% of vascular smooth muscle cells (VSMCs) (controls 0.8 (1.3)%; p < 0.001). Bax-IR was present in all specimens in 10 (5.4)% of medial cells (controls 0.3 (0.5)%; p < 0.001). Medial VSMCs (α-actin positive) with cytoplasmic staining for an apoptosis specific protein (c-jun/ASP) were present in 20/20 specimens (0.7 (0.6)% of VSMCs, controls 0%, p < 0.001), whereas terminal deoxynucleotidyl transferase mediated dUTP-biotin nick end labeling (TUNEL) positive VSMCs were present in 17/20 specimens (1 (1.5)% of VSMCs, controls 0%, p < 0.001). The presence of apoptosis was confirmed by electron microscopy and the demonstration of oligonucleosomal DNA fragments after agarose gel electrophoresis. As shown by double labeling and investigation of serial sections, p53-IR, Bax-IR, c-jun/ASP-IR, and positive TUNEL labeling localised to the same compartments of the aortic media, raising a possible role for p53 and Bax in the triggering of apoptosis of VSMC during CMD. MIB1/Ki-67 positive medial VSMCs (α-actin positive) and mesenchymal cells (vimentin positive) were present in all specimens (2.5 (2.8)% of medial cells; controls 0.3 (0.9)%, p < 0.001) mainly in the region around the vasa vasorum, indicating that cell regeneration during CMD may originate mainly from the mesenchyme surrounding the vasa vasorum. CONCLUSION: This study shows that the formal pathogenesis of CMD is characterised by p53 accumulation, Bax upregulation, cell death by apoptosis, and cell regeneration. Nevertheless, the precise stimuli of p53 activation and Bax upregulation as well as the role of p53 and apoptosis in the dissection process itself remain elusive.